Crystal structure of d‐stereospecific amidohydrolase from Streptomyces sp. 82F2 – insight into the structural factors for substrate specificity. (26th November 2015) - Arima, Jiro; Shimone, Kana; Miyatani, Kazusa; Tsunehara, Yuka; Isoda, Yoshitaka; Hino, Tomoya; Nagano, Shingo
Abstract : d ‐Stereospecific amidohydrolase (DAH) from Streptomyces sp. 82F2, which catalyzes amide bond formation fromd ‐aminoacyl esters andl ‐amino acids (aminolysis), can be used to synthesize short peptides with adl ‐configuration. We found that DAH can use 1, 8‐diaminooctane and other amino compounds as acyl acceptors in the aminolysis reaction. Low concentrations of 1, 8‐diaminooctane inhibited acyl‐DAH intermediate formation. By contrast, excess 1, 8‐diaminooctane promoted aminolysis by DAH, producingd ‐Phe‐1, 8‐diaminooctane via nucleophilic attack of the diamine on enzyme‐boundd ‐Phe. To clarify the mechanism of substrate specificity and amide bond formation by DAH, the crystal structure of the enzyme that binds 1, 8‐diaminooctane was determined at a resolution of 1.49 Å. Comparison of the DAH crystal structure with those of other members of the S12 peptidase family indicated that the substrate specificity of DAH arises from its active site structure. The 1, 8‐diaminooctane molecule binds at the entrance of the active site pocket. The electrkon density map showed that another potential 1, 8‐diaminooctane binding site, probably with lower affinity, is present close to the active site. The enzyme kinetics and structural comparisons suggest that the location of enzyme‐bound diamine can explain the inhibition of the acyl‐enzyme intermediate formation, although the bound diamine is too far from the active site for aminolysis. Despite difficulty in locating the diamine binding site for aminolysis definitively, we propose that the excess diamine also binds at or near the second binding site to attack the acyl‐enzyme intermediate during aminolysis. Database: The coordinates and structure factors ford ‐stereospecific amidohydrolase have been deposited in the Protein Data Bank at the Research Collaboratory for Structural Bioinformatics under code:3WWX . Abstract : D‐Stereospecific amidohydrolase (DAH) can use diamine as acyl acceptors in the aminolysis. Low concentrations of 1, 8‐diaminooctane inhibited acyl‐DAH intermediate formation, but excess 1, 8‐diaminooctane promoted aminolysis. The structural analysis suggests that the location of enzyme‐bound 1, 8‐diaminooctane can explain the inhibition of the acyl‐enzyme intermediate formation. In addition, the excess 1, 8‐diaminooctane is considered to bind to attack the acyl‐enzyme intermediate during aminolysis.